Fundamental of Entrepreneurship ENT300: Square Gear Enterprise/ Mohammad Aizzat Mohd Abd Hafiz ... [et al.] - Mohd Abd Hafiz, Mohammad Aizzat; Ghazali, Nur Akmal; Zikri, Mohd Ashrun Shadiran; Azahari, Mohd Shafiq Azha; Rosli, Nur Shazana (2019)
SQUARE GEAR is a company that sells basically three types of bicycle; mountain bike, BMX bike and fixed bike. The SQUARE GEAR Is located at. The administrative office and operational space are both in same business premise. This company will start its operation on 1 January 2012. The management team is headed by 6 experienced and professional level workers that will handle the management and operation of the company in order to get the best quality products and maximum profit. The managers are Mohammad Aizzat bin Mohd Abd Hafiz as General Manager, Nur Akmal bin Ghazali as Administration Manager, Mohd Ashrun Shadiran bin Zikri as Operation Manager, Mohd Shafiq Azha bin Azahari as Marketing Manager and Nur Shazana binti Rosli as Financial Manager. The total capital for SQUARE GEAR ENTERPRISE is RM 150,000. The company Is targeting total combined profits of RM 37,054 by the end of year three. In order to achieve this, the SQUARE GEAR ENTERPRISE’s strategies are to focus in the quality of the product and marketing plan. The Operation Manager and his assistant have been working hard to make sure the SQUARE GEAR ENTERPRISE’s product can satistied the customers. A comprehensive research has been made before producing the product to get the maximum quality needed. Customer's satisfaction is the first priority before profit.